Assessing Mentorship of Undergraduate Students at the University of Johannesburg: A Case-study - Nkomo, Morena William; Lokhele, Katlego; Hattingh, Teresa (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
The Faculty of Engineering and the Built Environment (FEBE) at the University of Johannesburg (UJ) has used mentoring to support students at the institution. In 2024, these initiatives were centralised and expanded to an integrated mentorship programme across the Faculty. All first-year students in the Faculty are allocated mentors drawn from volunteer senior students who wish to give back to their student community. The study explores the experiences of mentees and mentors in the programme to identify expected and experienced value. Furthermore, it explores and identifies challenges encountered and opportunities for further developing and refining the programme. A survey was conducted, inviting all the mentees and mentors who participated in the mentor programme during 2024. The survey was designed to elicit experiences on the programme from the perspective of the mentees and the mentors. This study presents the findings from the survey and provides insights that could be used to design mentorship programmes in similar contexts. The study also highlights the challenges experienced when implementing a Faculty-wide programme.